REPRODUÇÃO DO CAPITAL, TRANSIÇÃO SOCIAL E EMANCIPAÇÃO HUMANA - João Claudino Tavares (Revista de Políticas Públicas, 2009)
This paper analyzes the movement of the production and the reproduction of capital. The strength here is to identify the transition elements in the process of human emancipation. It is taken as an assumption that the material basis of production of wealth, explained in the full development of the productive forces of social work is the foundation and the expression of this transition, beyond men ́s willpower. It follows that the complete transition, that is, the realization of the realm of freedom is apparent from the inability of males to reproduce the bourgeois mediation and the full engendering new social and human relations.